Primary trauma care: a 20-year review. (October 2017) - Ley Greaves, RA; Wilkinson, LF; Wilkinson, DA
This year marks the 20th anniversary of the Primary Trauma Care Foundation (PTC), which provides a course aimed at providing a systematic approach to trauma and the unwell patient in low- and middle-income countries. The course is based on the original 36-page PTC manual and a key ethos of being appropriate to the target audience, affordable to those who need it, adaptable to the needs of each local area and sustainable to perpetuate itself. The concept is simple: a two-day course for candidates, followed by a one-day instructor course, and finally a first course delivered to local healthcare staff by the first cohort. Now in its 20th year, its reach spans 76 countries, is ingrained in the syllabus of many healthcare systems and continues to reach new territories with a programme shown to produce a measurable improvement in the care delivered.